Congenital absence of omentum with short bowel syndrome: a case report - Ramtin Naderian; Zahra Khatibian Feyzabadi; Paniz Bahoush; Samira Sanami; Mir Siamak Khatami (Journal of Medical Case Reports)
Abstract Introduction Short bowel syndrome can manifest as either an inherited or acquired condition, with the inherited form occurring sporadically. Furthermore, the complete absence of the omentum at birth (congenital absence) is a highly uncommon event. Case report This case report presents a unique confluence of these rare conditions in a 38-year-old Iranian male with a prior history of intestinal obstruction requiring right hemicolectomy and ileostomy. He subsequently presented to the emergency department experiencing intense abdominal pain and swelling in his lower extremities. Laboratory investigations revealed an elevated white blood cell count and metabolic alkalosis. During the surgical exploration prompted by his acute presentation, both congenital absence of the omentum and short bowel syndrome were confirmed. A jejunostomy was performed, but unfortunately, this intervention resulted in severe malabsorption and subsequent cachexia. This case sheds light on the rare occurrence of anastomotic leakage and subsequent peritonitis following right hemicolectomy and ileostomy in a patient with the combined conditions of congenital short bowel and congenital absence of the omentum. Conclusion This unique presentation highlights the potential complexities that can arise due to the convergence of these rare medical conditions.